Study of microflora petroleum stratal waters of deposits of Western Kazakhstan (Experimental biology, 2017)
The article provides quantitative and qualitative physical, chemical and microbiological characteristics petroleum stratal waters of the two working deposits «Zhetybai» and «Kulsary». The studies shows that petroleum stratal waters deposits «Zhetybai» and «Kulsary» have a neutral pH are highly mineralized, sodium-chlorine with the various quantitative indicators in the total mineralization and ion content of potassium, calcium, magnesium and sodium. It is established that aerobic microorganisms petroleum stratal waters deposits have environmental value of these ecosystems, as numerous, and, show active vital functions - 25,10х106 CFU/ml and 1,80х106 CFU/ml, respectively, whereas, the number of anaerobic microorganisms in samples of «Zhetibay» - 0,38х105 CFU/ml, and samples «Kulsary» - much smaller - 0,50х102 CFU/ml. Found that the formation waters contain the following groups of organisms: the spore microorganisms, micromycetes, Pseudomonas and representatives of the Bacillus, and actinobacteria and enterobacteria not detected.During works, from petroleum stratal waters of deposits of Western Kazakhstan 33 cultures of microorganisms that require a further study as perspective microorganisms for creation of technologies of secondary extraction of oil from petroleum layers are abstracted.
Keywords: microorganisms, enhanced oil recovery, stratal water, surfactant, emulsification index